(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Plant Garbage Juice (PGJ) is a highly concentrated bio-molecular solution. It contains water and bio-molecules such as acetic acid, sugar, proteins, alcohol, as well several enzymes like protease, amylase, lipase, and papain. It is promoted as a multifunctional solution for agricultural and domestic needs. In this investigation, two types of PGJ solutions were prepared to observe their various effects. The first one was prepared with mixed vegetable peels (PGJ-1) and the second with citrus peels (PGJ-2). Both solutions were acidic in nature, pH and EC (Electrical Conductivity) were detected as 4.3, 5.3 in PGJ-1, and 3.3, 2.58 in PGJ-2, respectively. PGJ-1 solution was applied to Aloe chinensis, a dwarf cultivar, and the growth rate was found to be higher than the control. In treatment 2 (T-2) of PGJ-1, the 2:1000 solution with water showed the best results for plant growth activities. The leaves of Aloe chinensis was found to turned brown green to dark green and the leaf thickness increased from 3.1 mm to 12.6 mm. The trash enzymes of PGJ solutions (I and II) exhibited antibacterial action against gram-positive and gram-negative bacteria, especially against pathogenic drug-resistant E. coli. PGJ-1 solution showed the highest zone of inhibition of 16 mm comparable to commercial antibiotic disk. PGJ solutions that have a catalytic enzyme showed the soil reconditioning process, such as a reduction of soil salinity. The mean of 20 soil samples showed that PGJ decreased the pH from 7.78 to 7.43. Similarly, the mean EC value of 20 soil samples also decreased from 0.45 ms/cm to 0.15 ms/cm. The pH and EC values of an alkaline sample also decreased significantly from 8.05 to 7.31 and 1.85 to 0.12, respectively. The results determined indicate that PGJ is a cost-effective plant growth-promoting factor and an eco-friendly substitute for minimizing global threats to agriculture. Plant Tissue Cult. & Biotech. 34(2): 237-245, 2024 (December)